The freshwater alga Mucidosphaerium sphagnale (Chlorellaceae: Chlorophyta) in New Zealand: the first record outside Europe - P. M. Novis (New Zealand Journal of Botany, 2017)
Mucidosphaerium sphagnale , a new record for New Zealand, is reported from Awarua Wetland. The genus Mucidosphaerium has recently been separated from the well‐known Dictyosphaerium , a colonial green alga with cells connected by thin, branching stalks, to encompass those forms with near‐spherical adult cells. The previous name for this taxon, Dictyosphaerium sphagnale , is not recorded from New Zealand; however, Mucidosphaerium pulchellum (syn. Dictyosphaerium pulchellum ), which has been reported here many times and is very difficult to distinguish without DNA sequences, may represent previously misidentified instances of M. sphagnale . The M. sphagnale is reported here from a Sphagnum bog, as is typical of its European range, whereas M. pulchellum in New Zealand appears to have been reported exclusively from lakes and rivers. The organism reported here is therefore quite likely a genuine new occurrence. Co‐introduction to New Zealand with foreign Sphagnum is a possibility.

Photosynthetic biocathode enhances the power output of a sediment‐type microbial fuel cell - AS Commault; G Lear; P Novis; RJ Weld (New Zealand Journal of Botany, 2014)
Conventional microbial fuel cells (MFCs) consist of biological anodes and abiotic cathodes separated by a proton‐exchange membrane. The abiotic cathode usually catalyses the reduction of oxygen to produce water by means of expensive catalysts such as platinum. 1 The cathodic reaction is often limiting in MFCs and researchers are now focusing on efficient, low‐cost catalysts to improve oxygen reduction at the cathode. This paper describes a photosynthetic biocathode in a sediment‐type MFC constructed without a proton‐exchange membrane. The carbon and stainless steel cathode did not contain any catalyst, but was covered in a biofilm composed of a complex community including microalgae and cyanobacteria. Although electroactive species were detected in the cathode biofilm, no biocatalysis of oxygen reduction was observed. Enhancement of the current output was mostly due to the production of pure oxygen near the cathode surface by the photosynthetic biofilm. Photosynthesis could produce dissolved oxygen levels approximately four times higher than oxygen levels obtained by aeration. The MFC was able to generate a maximum power density of 11 mW/m 2 (projected anode area) over six months without feeding.

Isotopic evidence for the provenance and turnover of organic carbon by soil microorganisms in the Antarctic dry valleys - D. W. Hopkins; A. D. Sparrow; E. G. Gregorich; B. Elberling; P. Novis; F. Fraser; C. Scrimgeour; P. G. Dennis; W. Meier‐Augenstein; L. G. Greenfield (Environmental Microbiology, 2009)
Summary The extremely cold and arid Antarctic dry valleys are one of the most environmentally harsh terrestrial ecosystems supporting organisms in which the biogeochemical transformations of carbon are exclusively driven by microorganisms. The natural abundance of 13 C and 15 N in source organic materials and soils have been examined to obtain evidence for the provenance of the soil organic matter and the C loss as CO 2 during extended incubation (approximately 1200 days at 10°C under moist conditions) has been used to determine the potential decay of soil organic C. The organic matter in soils remote from sources of liquid water or where lacustrine productivity was low had isotope signatures characteristic of endolithic (lichen) sources, whereas at more sheltered and productive sites, the organic matter in the soils that was a mixture mainly lacustrine detritus and moss‐derived organic matter. Soil organic C declined by up to 42% during extended incubation under laboratory conditions (equivalent to 50–73 years in the field on a thermal time basis), indicating relatively fast turnover, consistent with previous studies indicating mean residence times for soil organic C in dry valley soils in the range 52–123 years and also with recent inputs of relatively labile source materials.